Health-related quality of life and related factors in stroke survivors: Data from Korea National Health and Nutrition Examination Survey (KNHANES) 2008 to 2014 - Kwon, SuYeon (PLoS One, 2018)
As persons with stroke are surviving longer, monitoring and managing their quality of life is becoming important. We reviewed the Korea National Health and Nutrition Examination Survey (KNHANES) in order to evaluate the health-related quality of life (HRQoL) in stroke survivors as measured by the Euro Quality of Life-5D (EQ-5D), and to find out influencing factors. A total of 42,500 subjects were enrolled in the KNHANES, and 575 of them were persons with stroke. The EQ-5D index was lower in persons with stroke than those without stroke, when adjusted for age and sex (with stroke: 0.757±0.012, without stroke: 0.948±0.001, p < .0001). Dimension-specific influencing factors of HRQoL were observed in persons with stroke; mobility problems increased with old age; self-care problems increased with old age and depression; usual activity problems increased with old age, low income, absence of economic activity, and depression; pain/discomfort problems increased with low income. The EQ-5D index was lower in stroke survivors with older age, hypertension, diabetes mellitus, and lack of regular exercise. This is the first study to utilize nationally representative data of the Korean population to investigate the effect of stroke on HRQoL and explore the dimension-specific influencing factors. Further development of rehabilitative interventions for post-stroke depression, vocational rehabilitation, and tailored programs for encouraging physical activity may be needed to improve the HRQoL in Korean stroke survivors.